Pengaruh Likuiditas dan Leverage terhadap Profitabilitas Serta Dampaknya pada Harga Saham Sub Sektor Perbankan di Bursa Efek Indonesia - Doda, Nurain; Latjokke, Abd Gaffar; Sabir, Muh. (Melati Institute, 2025)
This study aims to analyze the effect of liquidity and leverage on profitability and their impact on stock prices in banking sub-sector companies listed on the Indonesia Stock Exchange for the period 2021–2023. Liquidity is measured using the Quick Ratio, leverage using the Debt to Equity Ratio (DER), and profitability using Return on Assets (ROA). Stock price, as the dependent variable, reflects the market’s perception of the company's financial performance. This research is motivated by the fluctuation in banking sector stock prices in the post-COVID-19 pandemic era, highlighting the importance of an in-depth analysis of companies’ fundamental factors. The study employs a quantitative approach with path analysis techniques to examine both direct and indirect relationships among variables. The results show that liquidity has a significant positive effect on both profitability and stock price. Meanwhile, leverage does not have a significant effect on profitability or stock price. Profitability is proven to have a significant effect on stock price and acts as a mediating variable between liquidity and stock price. These findings provide practical implications for investors and company management in making strategic decisions based on financial indicators.